Human capital investment expenditures of women of female-headed household in Peninsular Malaysia - Michael, Noorin Yuvarani; M. Munisamy, Thamarai; Haron, Sharifah Azizah; Chan, Benjamin Yin Fah (Canadian Center of Science and Education, 2010)
This study aims to investigate the human capital expenditure, expenditure share of human capital investment expenditure and the probability of having human capital investment among women of female-headed households. The data were obtained from a nationwide study on “Economic wellbeing and human capital investment of female-headed household” funded by the Ministry of Science, Technology and Innovation (MOSTI), government of Malaysia, under the e-Science Grant. Four states (Kedah, Pahang, Negeri Sembilan and Selangor) represents four zones were selected using simple random technique with 68% of response rate. The study found that women of female-headed household spent about 21% of their yearly income in reading material followed by health (18%) and personal care (15%). Similarly, expenditure share about 67% of their yearly income was spent on reading materials followed by health (63%) and personal care (58%) Further analysis revealed that those who have a higher household income (OR = 0.023; P<0.05) and smaller household size (OR = 0.028; P<0.05) were found to be significant invested part of their household expenses for their own human capital purposes.